The distribution of surpluses in legislation Argentina of cooperatives and its tax implications - Cracogna, Dante (Cooperativismo & Desarrollo, 2019)
Objective: about a project of tax reform, which finally did not prosper, aimed at taxing the surplus of the cooperatives with the income tax, the article analyzes the nature of such surpluses in the Argentine legislation to support its non-subjection to the tax.Methodology: the different legal aspects that differentiate the surpluses of the cooperatives from the earnings of societies in general.Results: in light of current regulations, the peculiar nature of cooperatives is defined and characterized by analyzing the mechanism that the law imposes for the determination of surpluses and the procedure for their distribution, as well As the characteristics of the cooperative capital and the form of its remuneration, the return to the associates in case of withdrawal and dissolution, and the constitution of reserves of an irreparable nature.Discussion and conclusions: it is pointed out that, ultimately, the associates individually are subject to the tax. Concludes by noting the growing risks that cooperatives face in this matter derived from their confusion with lucrative societies, as of ever increasing fiscal needs.
Keywords: cooperative capital; cooperatives; surpluses; taxes; reserves; returns